Analysis of Photocatalytic Properties of Poly(Methyl Methacrylate) Composites with Titanium(IV) and Ruthenium(III) Complexes - Kubiak, Barbara; Topolski, Adrian; Radtke, Aleksandra; Muzioł, Tadeusz; Impert, Olga; Katafias, Anna; van Eldik, Rudi; Piszczek, Piotr (Applied Sciences, 2025)
This study explores poly(methyl methacrylate) (PMMA)-based composites as potential alternatives to conventional TiO2-based photocatalysts. Specifically, it examines PMMA composites enriched with oxo–titanium(IV) complexes, [Ti8O2(OiPr)20(man)4] (1), [Ti4O(OiPr)10(O3C14H8)2] (2), and [Ti6O4(OiPr)2(O3C14H8)4(O2CEt)6] (3), alongside ruthenium(III) complexes, K[Ru(Hedta)Cl]∙2H2O (4) and [Ru(pic)3]·H2O (5). We assessed the physicochemical, adsorption, and photocatalytic properties of these composites with structural analyses (Raman spectroscopy, X-ray absorption (XAS), and SEM-EDX), confirming the stability of complexes within the PMMA matrix. Composites containing titanium(IV) compounds demonstrated notably higher photocatalytic efficiency than those with ruthenium(III) complexes. Based on activity profiles, composites were categorized into three types: (i) UV-light active (complexes (1) and (2)), (ii) visible-light active (complexes (4) and (5)), and (iii) dual-range active (complex (3)). The results highlight the strong potential of titanium(IV)–PMMA composites for UV-driven photocatalysis. Moreover, their activity can be extended to the visible range after structural modifications. Ruthenium(III)–PMMA composites, in turn, showed superior performance under visible light. Overall, PMMA composites with titanium(IV) or ruthenium(III) complexes demonstrate promising photocatalytic properties for applications using both UV and visible light ranges.
CRIS-Team Scopus Importer:2025-03-07
Keywords: adsorptive properties; photocatalytic activity; physicochemical properties; PMMA-based composites; ruthenium(III) complexes; titanium(IV)–oxo complexes